2018
DOI: 10.1002/cpt.1232
|View full text |Cite
|
Sign up to set email alerts
|

Rifampicin Alters Metformin Plasma Exposure but Not Blood Glucose Levels in Diabetic Tuberculosis Patients

Abstract: The pharmacokinetic (PK) and clinical implications of combining metformin with rifampicin are relevant to increasing numbers of patients with diabetic tuberculosis (TB) across the world and are yet unclear. We assessed the impact of rifampicin on metformin PKs and its glucose-lowering effect in patients with diabetic TB by measuring plasma metformin and blood glucose during and after TB treatment. Rifampicin increased metformin exposure: plasma area under the plasma concentration-time curve from time point 0 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“… 50 In addition to the medication’s adverse effects, the prior perception of the pill burden of taking too many medications is another important reason for abandoning treatment, underscoring the need to consider the patient’s belief and knowledge of their condition. 50 , 51 …”
Section: Tuberculosis and Diabetes: Twin Epidemicsmentioning
confidence: 99%
See 1 more Smart Citation
“… 50 In addition to the medication’s adverse effects, the prior perception of the pill burden of taking too many medications is another important reason for abandoning treatment, underscoring the need to consider the patient’s belief and knowledge of their condition. 50 , 51 …”
Section: Tuberculosis and Diabetes: Twin Epidemicsmentioning
confidence: 99%
“…Moreover, the situation gets worse as TB clinics often do not monitor DM blood markers through finger prick glucose testing or H1Abc blood levels, thereby not having the chance to detect uncontrolled DM in patients. 50 Given that it is known that DM comorbid condition is a risk factor for various negative TB outcomes, TB clinics should offer differentiated care for this type of patients, 51 , 52 as it is feasible to manage uncontrolled DM if detected early in TB treatment. All this highlights the importance of monitoring, educating, and counseling when dealing with medication adherence in TB-DM patients.…”
Section: Tuberculosis and Diabetes: Twin Epidemicsmentioning
confidence: 99%
“…Recently, it was shown that the exposure to antibiotics in childhood has been linked to increased risk of metabolic disorders later in life and associated with changes in development of pancreas[ 63 ]. Additionally, some antibiotics may alter the antidiabetic plasma levels; diabetic patients with tuberculosis were advised to take rifampicin and metformin with sufficient time interval[ 131 ]. Clarithromycin is another antimicrobial agent associated with severe hypoglycemia in diabetic patients receiving hypoglycemic medications, the risk increases with renal impairment and in elderly patients[ 132 ].…”
Section: Antimicrobials With Anti-diabetic Activitymentioning
confidence: 99%
“…Metformin is the first choice glucose-lowering agent recommended in type 2 diabetes, and there is no reason this should be different for patients with active TB disease. The advantages of metformin include extensive experience with the drug, extremely low risk of hypoglycaemia, effectiveness, low cost, beneficial effects on cardiovascular disease, [ 67 ] lack of clinically relevant interaction with rifampicin [ 70 ] and a potential benefit on TB itself [ 71 ]. In a recent retrospective analysis from Taiwan, those with diabetes (30%) had a 1.9 times higher mortality, but among this group, metformin use was associated with lower mortality (HR 0.56, 95% CI 0.39–0.82) [ 72 ].…”
Section: Treatment Of Combined Diabetes and Tuberculosismentioning
confidence: 99%